2020
DOI: 10.1016/j.bbmt.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Postremission Consolidation by Autologous Hematopoietic Cell Transplantation (HCT) for Acute Myeloid Leukemia in First Complete Remission (CR) and Negative Implications for Subsequent Allogeneic HCT in Second CR: A Study by the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation (EBMT)

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Passweg et al. reported that AML patients who received a second allo‐HSCT in CR2 with prior auto‐HSCT had higher risk of NRM compared to those who received chemotherapy consolidation before 21 . Our analysis showed that the auto‐HSCT group exhibited significantly better OS after relapse than the MSD‐HSCT and AD‐HSCT groups, however, it is important to exercise caution when interpreting the findings due to the small sample size of the population studied.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Passweg et al. reported that AML patients who received a second allo‐HSCT in CR2 with prior auto‐HSCT had higher risk of NRM compared to those who received chemotherapy consolidation before 21 . Our analysis showed that the auto‐HSCT group exhibited significantly better OS after relapse than the MSD‐HSCT and AD‐HSCT groups, however, it is important to exercise caution when interpreting the findings due to the small sample size of the population studied.…”
Section: Discussionmentioning
confidence: 58%
“…with prior auto-HSCT had higher risk of NRM compared to those who received chemotherapy consolidation before. 21 Our analysis showed that the auto-HSCT group exhibited significantly better OS after relapse than the MSD-HSCT and AD-HSCT groups, however, it is important to exercise caution when interpreting the findings due to the small sample size of the population studied. Shumilov et al reported that 80% of patients who relapsed after auto-HSCT could receive further curative-intent therapy, with approximately 60% of them proceeding to undergo allo-HSCT.…”
Section: Discussionmentioning
confidence: 65%
“…Autologous stem cell transplantation in CR1 has been shown to impact negatively the outcome following allogeneic transplant in CR2. 20,21 These two elements may have contributed to the increase of NRM in Haplo-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Also the haploidentical recipient group includes 10% of patients who had an autologous stem cell transplantation in CR1 versus less than 5% in the other two groups. Autologous stem cell transplantation in CR1 has been shown to impact negatively the outcome following allogeneic transplant in CR2 20,21 . These two elements may have contributed to the increase of NRM in Haplo‐HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on molecular and cytogenetic risk assessment conducted at the time of diagnosis and response to induction treatment, various consolidation therapy options are considered [ 1 ]. For good- and intermediate-risk patients, high-dose chemotherapy (HDCT) followed by autologous hematologic stem cell transplantation (ASCT) or chemotherapy consolidation are options, whereas the standard approach for adverse risk or MRD-positive, intermediate-risk patients is allogeneic stem cell transplantation [ 2 , 3 , 4 , 5 ]. HDCT/ASCT in MRD-negative and good- or intermediate-risk patients is effective and prolongs survival, with less toxicities as compared to allogeneic stem cell transplantation [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%